THE DEVELOPMENT OF BOCCIA BALL THROWING TEST INSTRUMENTS ON PALSY CEREBRAL ATHLETES - Doewes, Rumi Iqbal; Hendarto, Singgih; Adia, Pomo Warih; Shidiq, Abdul Aziz Purnomo; Ubaidillah,; Putroa, Baskoro Nugroho (International Journal of Psychosocial Rehabilitation, 2020)
Boccia is a accuracy game for cerebral palsy athletes. In the boccia game, the player will throw a red or blue leather ball with a target of the white ball (jack) target. The score of game is the closest colored ball to the white ball (jack) which counts points. Athletes experience throwing problems in approaching the white ball (jack), so it is necessary to develop instruments to measure throwing skills. This development research purpose was determined the boccia ball throwing test instrument in cerebral palsy athletes. The research subjects were 10 athletes. The research uses a development method through 4 stages such as data collection, product planning, model testing and validation. Research Analysis was used corrected item-total correlation analysis in SPSS through validity and reliability testing. The results showed tht the instrument validity by 6 throws testing, that is in the first throwing the validity value is 0.754; second throwing the validity value is 0.828; third throwing the validity value is 0.859; forth throwing the validity value is 0.742; fifth throwing the validity value is 0.789; and on sixth throwing the validity value is 0.779. The instruments reliability value is 0.918. The research conclusion is the development of boccia ball throwing tests instrument are valid and reliable so that it can be used to measure the accuracy of athletes’ skills in balls throwing of boccia.